26.2k views
5 votes
6^9 / 6^3 Please simplify I need help

User Gander
by
4.9k points

2 Answers

0 votes

Answer: 6^6

Step-by-step explanation: Formula - (a^b)/(a^c) = a^(b-c)

keeping the formula in mind;

= 6^9/6^3= 6^(9-3)

= 6^6

User Thushara
by
5.5k points
7 votes

Answer:

6^6

Explanation:

The applicable rule of exponents is ...

(a^b)/(a^c) = a^(b-c)

In this problem, that means ...

(6^9)/(6^3) = 6^(9-3) = 6^6

__

It can help to remember that an exponent signifies repeated multiplication. Written out without exponents, the problem is ...


(6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6\cdot6)/(6\cdot6\cdot6)=6\cdot6\cdot6\cdot6\cdot6\cdot6=6^6

Note that the 3 instances of 6 in the denominator cancel 3 from the numerator. Clearly, the effect is the same as subtracting exponents.

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.